Valorization of aluminothermite welding slag in sustainable high-performance heavyweight concrete: mechanical and radiation performance - Albayrak, Enes Burak; Yuzer, Nabi; Dinc-Sengonul, Burcu (ELSEVIER, 2026)
The growing demand for radiation-shielding materials in nuclear, medical, and protective infrastructures has intensified interest in sustainable alternatives to conventional heavyweight aggregates. This study investigates the valorization of aluminothermite welding slag (AWS), a dense oxide-rich industrial by-product generated at 2200-3000 degrees C, as a heavyweight aggregate in high-performance concrete (HPC). Six concrete mixtures incorporating 0-100 % AWS were produced at a constant water-to-binder ratio of 0.18, including both fiber-free and steel-fiber-reinforced (0.6 vol %) series. Mechanical performance, fracture behavior, microstructure, capillary water absorption, and gamma and neutron radiation-shielding performance were systematically evaluated. The full-replacement mixture (ALM100) achieved an oven-dry density of 2624 kg/m3 and a 28-day compressive strength of 117 MPa, representing a 12.5 % increase compared to the fiber-reinforced reference. Flexural strength and fracture energy increased to 16 MPa and 1205 N/m, respectively, indicating enhanced post-cracking ductility. Gamma-ray shielding tests using a 0.662 MeV Cs-137 source showed that the linear attenuation coefficient increased from 0.139 cm-1 (REF) to 0.167 cm-1 (ALM100), accompanied by reduced half-and tenth-value layers. Neutron attenuation also improved with increasing AWS content. SEM-EDS analyses confirmed matrix densification and the formation of Fe-Al-Mn oxide-rich clusters responsible for both mechanical enhancement and radiation attenuation. A cradle-to-gate CO2 assessment revealed that AWS-based heavyweight concrete exhibits approximately 21-29 % lower embodied carbon than conventional barite-, magnetite-, and hematite-based concretes. Furthermore, an Eco-Strength Efficiency (ESE) analysis demonstrated that the AWS-HPC achieved the highest mechanical performance per unit of embodied carbon among the investigated mixtures. Overall, the results confirm that AWS is a technically viable and environmentally efficient aggregate for producing multifunctional heavyweight concretes for structural and radiation-shielding applications.
Keywords: Aluminothermite welding slag (AWS); High-performance concrete (HPC); Heavyweight concrete; Radiation shielding; Nuclear safety; Sustainability; CEMENTITIOUS COMPOSITES HPFRCC; FIBER-REINFORCED CONCRETE; HIGH-STRENGTH CONCRETE; ATTENUATION COEFFICIENTS; STEEL; RAY; Chemistry; Science & Technology - Other Topics; Environmental Sciences & Ecology